Changes of CD4+ CD25+ Regulatory T Cells, FoxP3 in Adjuvant Arthritis Rats with Damage of Pulmonary Function and Effects of Tripterygium Glycosides Tablet. (27th December 2012) - Lei, Wan; Jian, Liu
Abstract : Objective . To observe the effects of tripterygium glycosides tablet (TPT) on swelling degree, arthritis index (AI), pulmonary function, cytokines, the expression of regulatory T cells (Treg), and Foxp3 in rats of adjuvant arthritis. Methods . Rats were averagely divided into normal control (NC) group, model control (MC) group, methotrexate (MTX) group, and tripterygium glycosides tablet (TPT) group. Except for the rats of normal group, the others were intracutaneously injected with 0.1 mL of Freund's complete adjuvant in the right hindlimb. NC group and MC group were treated with physiological saline. MTX group and TPT group were treated with MTX, TPT, respectively. Results . The levels of swelling degree, AI, the alveolar inflammation integral, TNF alpha (TNF-α ), and endothelium-1 (ET-1 ) in MC group were significantly increased (P < 0.01 ), and the levels of forced vital capacity (FVC), 25% vital capacity of the peak expiratory flow (FEF25 ), 50% vital capacity of the peak expiratory flow (FEF50 ), 75% vital capacity of the peak expiratory flow (FEF75 ), maximum midexpiratory flow (MMF), peak expiratory flow (PEF), interleukin-10 (IL-10), CD4 + CD25 + Treg, and Foxp3 were decreased (P < 0.01 ). The scores of alveolitis and ET-1 were decreased with treatment of TPT. The levels of FVC, FEF25, FEF50, FEF75, MMF, PEF, IL-10, and CD4 + CD25 + Treg in peripheral blood were increased. The expressions of Foxp3 protein and mRNA in lung tissue were also increased in TPT group. Conclusions . The paw swelling can be inhibited by TPT, and the inflammatory response in lung tissue was also decreased, which is a significant improvement in pulmonary function. The mechanism is probably associated with upregulating the expression of IL-10, Foxp3, and downregulating the level of TNF-α .